1991
DOI: 10.1364/ao.30.002975
|View full text |Cite
|
Sign up to set email alerts
|

Absolute optical ranging using low coherence interferometry

Abstract: We describe a method for measuring submicrometer distances with an asymmetric fiber Michelson interferometer having an LED as a source of radiation. By measuring the phase slope of the Fourier components in the frequency domain, it is possible to locate the position of reflections with nanometer precision even in the presence of sample dispersion. The method is compatible with time domain sampling at the Nyquist rate which assures efficiency in data acquisition and processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(39 citation statements)
references
References 11 publications
0
38
0
1
Order By: Relevance
“…Theoretical analysis has shown that for a light source with a Gaussian spectrum, the width of the field autocorrelation function increases according to [ 9 ]: with the group velocity dispersion (GVD) D defined as where σ t is the 1/e 1/2 half width of the autocorrelation function, and σ t0 is the 1/e 1/2 half width of the autocorrelation function when D is zero. The 1/e 1/2 half width of the light spectrum is σ w , and ω 0 is the central frequency of the light spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical analysis has shown that for a light source with a Gaussian spectrum, the width of the field autocorrelation function increases according to [ 9 ]: with the group velocity dispersion (GVD) D defined as where σ t is the 1/e 1/2 half width of the autocorrelation function, and σ t0 is the 1/e 1/2 half width of the autocorrelation function when D is zero. The 1/e 1/2 half width of the light spectrum is σ w , and ω 0 is the central frequency of the light spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…En négligeant les termes de bruit, l'intensité optique détectée par la photodiode est définie comme une moyenne temporelle du module au carré du champ électrique total: (4) a: étant la proportion de l'intensité lumineuse du faisceau incident qui est couplée dans le bras test, a3 celle couplée dans le bras de référence. Si le système est considéré sans pertes : a~+ a~= I.…”
Section: Rappels Théoriquesunclassified
“…Powerful manufacturing techniques have been established for rapid and high precision fabrication of these devices. But online inspection, defect detection and measurement of height, shape and size requires equally powerful measurement techniques [1][2][3][4][5][6][7][8]. For fast, large area and precise measurement of surface height, defect detection and other morphological features a reliable, non-contact, non-invasive and fast measurement technique is required for aforementioned parameters.…”
Section: Introductionmentioning
confidence: 99%